An atlas of genetic regulation and disease associations of microRNAs - Ghanbari,M; Mustafa,R; Mens,M; Hilten,AV; Huang,J; Roshchupkin,G; Huan,T; Broer,L; Elliott,P; Levy,D; Ikram,MA; Evangelou,M; et al. (2022)
Abstract MicroRNAs (miRNAs) are small non-coding RNAs that post-transcriptionally regulate gene expression. Identification of genetic variants influencing the transcription of miRNAs can provide an understanding of their genetic regulation and implication in human disease. Here we present genome-wide association studies of 2,083 plasma circulating miRNAs measured by next-generation sequencing in 2,178 participants of the Rotterdam Study to identify miRNA-expression quantitative trait loci (miR-eQTLs). We report 4,310 cis- and trans-miR-eQTLs for 64 miRNAs that have been replicated across independent studies. Many of these miR-eQTLs overlap with gene expression, protein, and metabolite-QTLs and with disease-associated variants. The consequences of perturbation in miRNA transcription on a wide range of clinical conditions are systematically investigated in phenome-wide association studies, with their causality tested using Mendelian randomization. Integration of genomics and miRNAs enables interrogation of the genetic architecture of miRNAs, revealing their clinical importance, and providing valuable resources for future studies of miRNAs in human disease.